Won't You Be My Kissaroo? - Ryder, Joanne; 1956-; Sweet, Melissa (Boston, 2015)
Rhyming text describes many different kinds of kisses.
Keywords: Juvenile fiction; Kissing; Fiction; Juvenile works; Stories in rhyme; Fiction